PENGARUH EKSPOR NIKEL, MINYAK MENTAH SERTA INVESTASI ASING SEKTOR PERTAMBANGAN TERHADAP CADANGAN DEVISA MELALUI PDB SEKTOR PERTAMBANGAN DI INDONESIA - Alisya, Jeane; Armin Rahmansyah Nasution (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of nickel exports, crude oil exports, and foreign investment in the mining sector on Indonesia's foreign exchange reserves, with mining sector GDP as an intervening variable. The research method used in this study is a quantitative approach with path analysis. The research period covers 2005 to 2024 with data sources for foreign exchange reserves obtained from the World Bank, GDP for the mining sector obtained from the Indonesian Ministry of Agriculture, while nickel exports, crude oil exports and foreign investment in the mining sector were obtained from the Indonesian Central Statistics Agency. The study results indicate that nickel exports have a negative but insignificant effect on Indonesia's mining sector GDP and foreign exchange reserves. Crude oil exports have a negative and significant effect on both mining sector GDP and foreign exchange reserves. Meanwhile, foreign investment has a significant and positive effect on mining sector GDP but a negative and insignificant effect on Indonesia's foreign exchange reserves. Furthermore, mining sector GDP has a significant and positive effect on Indonesia's foreign exchange reserves. The indirect effect study indicates that mining sector GDP does not mediate the effect of nickel exports on foreign exchange reserves. However, mining sector GDP does mediate the effect of crude oil exports and foreign investment in the mining sector on Indonesia's foreign exchange reserves.